Kognat Bahasa Jawa dan Bahasa Bali: Sebuah Studi Kontrastif - I Dew Putu Wijana (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2021)
This article is about a contrastive analysis of Javanese and Balinese cognates, the two genetically related local languages spoken in Indonesia. Using data extracted from a Javanese dictionary and compared with their Balinese equivalents retrieved from my intuitions as a Balinese native speaker, it is found that even just from A and B entries, the two languages share a lot of cognates which are hypothetically derived from theirs descending language, proto language, Austronesian. In spite of cognates that have identically semantic contents and formal appearances, there also ones that have different phonological forms and semantic senses.